Drop jumps improve repeated sprint ability performance in professional basketball players - Zagatto, Alessandro Moura [UNESP] (2022)
To verify the acute effect of drop jumps (DJ) on two repeated sprint ability tests (RSA), interspersed with a rest period simulating a basketball game break. Twelve first division basketball players (age: 24.8 ± 6.9 years; body mass: 97.0 ± 9.2 kg; height: 2.0 ± 0.1 m) performed, in a randomized crossover design, two RSA tests separated by 5 min after DJ or control conditions. The DJ condition comprised 5 DJs performed 4 min prior to the first RSA test, whereas 3 DJ were completed 30 s prior to a second RSA test. Surface electromyography was recorded from the lower body for root mean square (RMS) analyses during sprinting. Three countermovement jump (CMJ) tests were performed after warming up and immediately after the second RSA test. DJ improved RSA performance with a faster best time in the first RSA test (p = 0.035), and a shorter total time and mean time (p = 0.030) for the second RSA test. No significant differences were found in RMS between protocols. CMJ decreased in both conditions after the RSA tests (p < 0.05). This study revealed a post-DJ RSA potentiation in professional male basketball players. This simple and effective approach could be implemented at the end of the warm-up and before the end of game breaks to improve player preparedness to compete.